Про початок використання грошової монети в Україні - Козубовський, Г.А. (Археологія, 2018)
Проаналізовано знахідки венеціанських гроссо ХІІІ— ХІV ст. в Україні. Звернуто увагу на негативні наслідки монгольської навали на розвиток грошового обігу. The study of the finds of Venetian coins and literary sources allows to make some previous remarks on the character of the goods-coinage relations on the territory of South Rus before the Mongol invasion. In the first part of 13th century new coins — denarii grosso began to struck in many centres of Italy. They had opened a new grosso period in Europe. The finds of Venetian grosso of the 13th—14th centuries on the territory of Ukraine are examined in the paper. The Venetian grosso of Enrico Dandolo (1192—1205) and Pietro Ziani (1205—1228) were found in Kyiv. However, Venetian silver grosso of the 13th century appeared into Rus restrictedly. They are absent in the hoards. In the first part of the 13th century Kyiv was the сеnter visited by Italian, Austrian, German, Polish, Silesian and other merchants. Mongol invasion stopped the process of entering to grosso period. The Venetian grosso of Raneri Geno (1252— 1266) and Francesco Dandolo (1328—1339) were found at the caravan travelling routs between Lviv and Kaffa and are connected with Black Sea trade. Анализ находок венецианских монет и письменных источников позволяет сделать некоторые предварительные замечания о товарно-денежных отношениях на территории Южной Руси перед монгольским нашествием. В первой половине XIII ст. новые монеты — (денарии) гроссо начинают чеканить во многих центрах Италии. Они открывают новый период гроша в Европе. В работе рассматриваются находки венецианских гроссо XIII—XIV вв. на территории Украины. Венецианские гроссо Енрико Дандоло (1192—1205) и Петро Зиани (1205—1228) были найдены в Киеве. Но венецианские гроссо попадают на Русь в ограниченном количестве. Они не откладываются в кладах. В первой половине XIII ст., Киев был центром, который посещали торговцы из Италии, Австрии, Польши, Германии, Силезии и других стран. Монгольское нашествие остановило процесс вхождения в период гроша. Венецианские гроссо Ранерия Джено (1252—1266), Франческо Дандоло (1328—1339) были найдены на караванном пути между Каффой и Львом и связываются с торговлей на Черном море.